Exfoliation of Graphene by Dendritic Water-Soluble Zinc Phthalocyanine Amphiphiles in Polar Media - Methfessel, Christian; Volland, Michel; Brunner, Kristin; Wibmer, Leonie; Hahn, Uwe; De La Torre, Gema; Torres, Tomas; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2018)
Two zinc phthalocyanines (ZnPcs) have been equipped with Newkome-type dendritic branches of increasing size and number of terminal carboxylate functional groups. The negatively charged carboxylates render these polyelectrolytes soluble in polar media such as methanol or buffered water. Sonication of the ZnPcs with graphene allowed for pronounced non-covalent binding of the ZnPc moieties on the graphene surface. These hybrid systems were fully characterized via UV/Vis, AFM, TEM, Raman and transient absorption spectroscopy, yielding insights into the electron donating nature of the novel phthalocyanine structures.
Keywords: dendrimers; donor-acceptor system; energy transfer; exfoliation; graphene

Synthesis and Aggregation of Amphiphilic Porphyrin-Perylenebisimide Dyads - Schulze, Erik; Wu, Mingjian; Methfessel, Christian; Spiecker, Erdmann; Hirsch, Andreas (Chemistry - A European Journal, 2025)
We report the straightforward synthesis of a family of amphiphilic zinc-porphyrin-perylenebisimide (PBI) dyads containing sterically demanding substituents at the porphyrin meso-position, as well as at the PBI bay-position. The hydrophilic head group consists of oligo-carboxylic acid G2-Newkome dendrons attached to the porphyrin, whereas lipophilic pentyl-hexyl-swallowtails are connected to the PBI imide position. Using UV/Vis absorption and fluorescence emission spectroscopy, their tetrahydrofuran (THF) initiated disaggregation was studied in aqueous media. Without meso-substituents, a stronger interaction between the porphyrins was observed in the aggregated state. Insights into the size and morphology of the aggregates were obtained by dynamic light scattering (DLS) and scanning transmission electron microscopy (STEM). Supported by density functional theory (DFT) calculations, these revealed micelles and liposomes as plausible architectures.
CRIS-Team Scopus Importer:2025-05-16
Keywords: aggregation; amphiphiles; donor-acceptor-hybrids; perylenebisimide; porphyrinoids

Synthesis and structure of tetraarylcumulenes: Characterization of bond-length alternation versus molecule length - Januszewski, Johanna; Wendinger, Dominik; Methfessel, Christian; Hampel, Frank; Tykwinski, Rik (Angewandte Chemie International Edition, 2013)
BLA=0? Not so fast! A series of tetraarylcumulenes up to the length of a [9]cumulene has been synthesized and analyzed by X-ray crystallography. The structural data show a distinct reduction in bond-length alternation (BLA) as a function of molecule length, but this trend appears to reach a limit before a cumulenic structure with BLA=0 is achieved. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.